PERBEDAAN KONSEP DIRI REMAJA PUTRI DAN REMAJA PUTRA YANG MENGALAMI ACNE - Nugroho, Christianto (Jurnal AKP, 2013)
Male and female teenager have different opinion teenager in looking them selves as an individual who experienced acne. Most teenager expenenced acne on un confidence face and felt sky. So that the teenager who experienced it usually having trouble of self concept. Especrally in self image and self concept.  The purpose of this study was to determine the differences of young male and female teenager in self-concept who get acne at SMA Negeri 1 Purwoasri.The research design used is study of comparative. Population of all grade 1 and grade 2 who experienced acne at SMA Negeri 1 Purwoasri totaled 94 respondents, a purposive sampling technique samples obtained 42 respondents male and 42 young female. Data were collected by questionnaires and processed by percentage analysis which were  presented in the form pie diagram and analysis used is Mann-Whitney U-Test.From the results which got obtained research young male who experience acne with a negative self-concept there were 27 respondents (32%), while the rate for female with a negative self-concept by 18 respondents (21%). So the differences of young male and female teenager in self-concept who get acne at SMA Negeri 1 Purwoasri Year 2013. Because significant  p smaller than α (0.029 <0.05).This is due to the young male in general have a high interest in appearance than the female.Concluded acne caused a low in teenager self-concept. It is recommended so that teenagers remain actively participate in various activities in order to keep a positive self-concept despite having acne on the face. It also set the stressor management that are not easily have a negative self-concept. Keywords: self-concept, teenagers, acne